METHODS OF ASSISTANCE FOR SMOKING CESSATION IN INTERNATIONAL CLINICAL RECOMMENDATIONS FOR TREATMENT AND PREVENTION OF CARDIOVASCULAR DISEASE - M. S. Berezhnova (Столичная издательская компания, 2016)
A review of international recommendations, including methods to assist in smoking cessation is presented. Particular attention is paid to the recommendations for treatment and prevention of cardiovascular disease. There are a lot of approaches to drop smoking including innovative pharmacotherapy. Implementation of these approaches is rational at all steps of health care for cardiovascular patients.